1988
DOI: 10.3171/jns.1988.69.4.0562
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatment with U-74006F on neurological outcome following experimental spinal cord injury

Abstract: The compound U-74006F is one of a series of 21-aminosteroids that lack glucocorticoid or mineralocorticoid activity. These potent inhibitors of lipid peroxidation have been specifically developed for the acute treatment of central nervous system trauma and ischemia. This study evaluated the dose-response characteristics and capability of U-74006F to promote functional recovery in cats subjected to compression trauma of the upper lumbar (L-2) spinal cord. Thirty minutes following injury, randomized and investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(31 citation statements)
references
References 35 publications
2
27
0
2
Order By: Relevance
“…2 The dose-response characteristics and capability of U-74006F to promote functional recovery in cats subjected to compression trauma of the upper lumbar (L-2) spinal cord have also been evaluated. 58 Results showed that over a 100-fold range of doses, U-74006F has a remarkable capacity to promote functional recovery in spinal cord injured cats. The mechanism of protective action of U-74006F against SCI is believed to involve an inhibition of oxygen radical-mediated lipid peroxidation.…”
Section: Nucleusmentioning
confidence: 98%
“…2 The dose-response characteristics and capability of U-74006F to promote functional recovery in cats subjected to compression trauma of the upper lumbar (L-2) spinal cord have also been evaluated. 58 Results showed that over a 100-fold range of doses, U-74006F has a remarkable capacity to promote functional recovery in spinal cord injured cats. The mechanism of protective action of U-74006F against SCI is believed to involve an inhibition of oxygen radical-mediated lipid peroxidation.…”
Section: Nucleusmentioning
confidence: 98%
“…5,6 Inhibition and scavenging of ROS production have been demonstrated to increase functional recovery following traumatic CNS injuries, thereby suggesting that enhanced ROS production contributes to SCI-mediated neuronal cell damage and neurological dysfunction. 7,8 Neurons are the most oxidative stress-susceptible cell type in the CNS. Both necrosis and apoptotic neuronal cell death have been detected in mouse and rat models following traumatic brain injury and/or SCI.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the discovery and development of more potent steroidal LP inhibitors, the 21-aminosteroids or "lazaroids," which lack the glucocorticoid receptor-mediated side effects that limit the clinical use of high-dose MP. One of these, tirilazad (also known as U-74006F), was selected for development based on its beneficial effects in animal SCI models [60,94,95].…”
Section: Tirilazad: a 21-aminosteroid Antioxidant Devoid Of Glucocortmentioning
confidence: 99%